Semantic Frameworks for e−Government - Crichton, C; Davies, J; Gibbons, J; Harris, S; Shukla, A (ACM, 2007)
This paper explains how semantic frameworks can be used to support successful e-Government initiatives by connecting system design to a shared understanding of interactions and processes. It shows how metadata standards and repositories can be used to establish and maintain such an understanding, and how they can be used in the automatic generation and instantiation of components and services. It includes an account of a successful implementation at an international level, and a brief review of related approaches.